Escarpments within Mediterranean seagrass Posidonia oceanica meadows increase habitat heterogeneity and structural complexity enhancing fish diversity and biomass - Gomis, Enric; Ballesteros, Enric; Bernabeu, Irene; Inostroza, Karina; Mateo, Miguel A.; Serrano, Oscar (Frontiers in Marine Science, 2024)
Seagrass meadows provide important ecosystem services including carbon sequestration, coastal protection from erosion, and sustained biodiversity and fisheries thereby improving the wellbeing and livelihoods of coastal communities. The erosion of millenary deposits of intertwined roots and rhizomes of Posidonia results in the formation of three-dimensional structures named escarpments that constitute a biogenic reef habitat. However, the natural history of seagrass escarpments including their formation processes and their role as habitat for reef fauna and flora remains poorly understood. This research located and characterized Posidonia oceanica escarpments in Menorca (Balearic Islands) and compared structural complexity and fish assemblages among seagrass escarpments, seagrass meadows, rocky substrates and bare sand with emphasis on its role as habitat and shelter for typical rocky fish. Fish abundance and biomass were similar between seagrass escarpments and rocky substrates (P > 0.05), but significantly lower in seagrass meadows (P < 0.001). The large number of caves found along seagrass escarpments provide shelter to fish, including species only associated to rocky substrates. Seagrass meadows form a rather homogenous habitat within their canopy, but the presence of seagrass escarpments enhances habitat heterogeneity and structural complexity along with fish abundance and biomass at the seascape level. This study enhances understanding on the ecological importance of seagrass escarpments.